Esthetic restoration of maxillary incisors using CAD/CAM chairside technology: case report - Seydler, Bodo; Schmitter, Marc (Quintessence international, 2011)
High-quality esthetic veneers can be produced in a single treatment session only by means of chairside CAD/CAM technology. With efficient therapy, the duration of the relatively long treatment cycle can be optimized: planning casts and a diagnostic wax-up are steps that simplify therapy decisions, ...